FAKTOR-FAKTOR LINGKUNGAN FISIK RUMAH YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH PUSKESMAS PASAR MINGGU JAKARTA SELATAN - Ayu Cintya Paraswati; Suhartono Suhartono; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Pneumonia is one of the main cause of death in infants aged less than 5 years. According to poli MTBS, pneumonia is a top five disease in Pasar Minggu Primary Health Care. The purpose of this research is to know the factors of the physical environment condition related to the incidence of pneumonia on infants. This research is a type of observational analytic study design with case-control study. The number of samples is 86 respondents who comprise 43 respondents group of cases and 43 respondent a control group, who are selected by the method of purposive sampling. Data analysis in this research used Chi Square test and see a big risk with Odds Ratio. The results of this study of the 9 variables examined there is no variable associated with the incidence of pneumonia in infants, but 1 variable is risk factor, natural pencahyaan in home (p-value = 0.035; Or = 4.040; 95% CI 1,027-15,901). So it can be inferred natural lighting does’t have significant relations, however represents a risk factor for the occurrence of pneumonia in infants. Therefore, always keep the House clean and healthy, like opening the Windows in the morning and evening or use the Sun's light translucent roof. It is important to avoid pneumonia prevention in infants.